(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Myelolipoma is a rare benign tumour composed of mature adipose tissue and nonnal haemopoietic elements. Although it can occur in extra-adrenal sites, it typically occurs in the adrenal glands. Being small and asymptomatic in most cases, myelolipomas are incidentally discovered at autopsies and now-a-days. by imaging. The tumour becomes symptomatic when it attains a large size, when it ruptures, or when it is associated with endocrine abnormalities of the adrenals. We report three cases of adrenal myelolipoma with symptoms like abdominal pain and discomfort, obesity and hypertension. One of the cases also had a co-incidental Ilydatid cyst of liver. Diagnosis of myelolipoma was suspected on imaging (computed tomography and ultrasound scan) and was confirmed by histopathology. The patients were followed up for one year after surge1y. One patient was found well and symptomless. One sustained hypertension but was otherwise healthy. The remaining patient, who had hypertension and renal complications previously, developed fluctuating hypertension and chronic renal failure about six months after operation.